A comparative study of combustion and emission characteristics of butanol isomers on a diesel engine with dual fuel butanol isomers/diesel compound combustion. (15th October 2019) - Xia, Qi; Wang, Kui; Han, Zhiqiang; Tian, Wei
Highlights: The combustion and emissions are compared between three isomers of butanol with BDCC mode. The constant volume combustion of n-butanol is more prominent in all isomers around TDC. The heat release time of n-butanol is more earlier than other isomers with BDCC mode. The ignition delay of n-butanol is obviously shorter than other isomers with BDCC mode. Abstract: Combustion and emission characteristics of butanol isomers were experimentally investigated on a four-cylinder common-rail diesel engine, which was modified to operate in butanol/diesel compound combustion (BDCC) mode. Butanol isomers were utilized as a renewable fuels to alleviate the consumption of fossil fuels by replacing diesel, the substitution ratio was defined as the ratio of the quantity of diesel replaced by butanol isomers to the original diesel quantity. The combustion and emission characteristics were compared by using neat diesel, n -butanol, iso -butanol, and sec -butanol. The engine speeds were set at 2250 r/min, and the engine loads were set at 25%, 50%, 75%, and 100%. The experimental results demonstrate that spontaneous combustion of butanol isomers occur before diesel injection, and n -butanol firstly reaches spontaneous combustion. Auto-ignition of n -butanol occurs more easily than it does for iso -butanol and sec -butanol, which is determined that the heat release start time of n -butanol is earlier than iso -butanol and sec -butanol in the BDCC mode during cylinder combustion. The order of maximum combustion temperatures is n -butanol > sec -butanol > iso -butanol. The order of ignition delay time is sec -butanol ≈ iso -butanol > n -butanol, and the constant volume combustion of n -butanol is more evident than that of iso -butanol and sec -butanol close to TDC. The NOx and soot emissions of n -butanol are generally higher than those of iso -butanol and sec -butanol in BDCC mode. The THC and CO emissions of n -butanol are both lower than those of iso -butanol and sec -butanol, but the difference becomes less obvious with increasing load.